Using accreditation surveyors to conduct health services research: a qualitative, comparative study in Australia. (5th February 2020) - Winata, Teresa; Clay-Williams, Robyn; Taylor, Natalie; Hogden, Emily; Hibbert, Peter; Austin, Elizabeth; Braithwaite, Jeffrey
Abstract: Objective: Healthcare accreditation surveyors are well positioned to gain access to hospitals and apply their existing data collection skills to research. Consequently, we contracted and trained a surveyor cohort to collect research data for the Deepening our Understanding of Quality in Australia (DUQuA) project. The aim of this study is to explore and compare surveyors' perceptions and experiences in collecting quality and safety data for accreditation and for health services research. Design: A qualitative, comparative study. Setting and Participants: Ten surveyors participated in semi-structured interviews, which were audio recorded, transcribed and coded using Nvivo11. Interview transcripts of participants were analysed thematically and separately, providing an opportunity for comparison and for identifying common themes and subthemes. Intervention(s): None. Main Outcome Measure(s): Topics addressed data collection for healthcare accreditation and research, including preparation and training, structure, organization, attitudes and behaviours of staff and perceptions of their role. Results: Five themes and ten subthemes emerged from the interviews: (1) overlapping facilitators for accreditation and research data collection, (2) accreditation-specific facilitators, (3) overlapping barriers for accreditation and research data collection, (4) research data collection-specific barriers and (5) needs and recommendations. Subthemes were (1.1) preparation and training availability, (1.2) prior knowledge and experiences; (2.1) ease of access, (2.2) high staff engagement, (3.1) time, (4.1) poor access and structure, (4.2) lack of staff engagement, (4.3) organizational changes; (5.1) short-notice accreditation and (5.2) preparation for future research. Conclusions: Although hospital accreditation and research activities require different approaches to data collection, we found that suitably trained accreditation surveyors were able to perform both activities effectively. The barriers surveyors encountered when collecting data for research provide insight into the challenges that may be faced when visiting hospitals for short-notice accreditation.